2022
DOI: 10.1371/journal.ppat.1010550
|View full text |Cite
|
Sign up to set email alerts
|

PI Kinase-EhGEF2-EhRho5 axis contributes to LPA stimulated macropinocytosis in Entamoeba histolytica

Abstract: Entamoeba histolytica is a protozoan responsible for several pathologies in humans. Trophozoites breach the intestinal site to enter the bloodstream and thus traverse to a secondary site. Macropinocytosis and phagocytosis, collectively accounting for heterophagy, are the two major processes responsible for sustenance of Entamoeba histolytica within the host. Both of these processes require significant rearrangements in the structure to entrap the target. Rho GTPases play an indispensable role in mustering prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 109 publications
(148 reference statements)
0
7
0
Order By: Relevance
“…The fluorescence recovery was analyzed using Cell Sens software (Olympus), where the half-lifetime ( τ 1/2 ) was determined as the time at which 50% fluorescence recovery occurred. The following double exponential fit equation was used for analyzing the recovery curves: 34 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fluorescence recovery was analyzed using Cell Sens software (Olympus), where the half-lifetime ( τ 1/2 ) was determined as the time at which 50% fluorescence recovery occurred. The following double exponential fit equation was used for analyzing the recovery curves: 34 …”
Section: Methodsmentioning
confidence: 99%
“…For further analysis of droplet images, ImageJ soware was used. 34 2.2.7 Fluorescence recovery aer photobleaching (FRAP). FRAP experiments were carried out on an Olympus FV3000 confocal microscope using a FRAP module.…”
Section: 24mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that LPA signaling remodels actin dynamics ( Mir et al, 2020 ) and that the actin cytoskeleton is involved in membrane trafficking ( Lanzetti, 2007 ), the defects in intracellular membrane trafficking in Enpp2 −/− VE cells are likely related to and caused by dysregulation of the Rho-ROCK-LIM kinase pathway. Association between LPA and membrane trafficking was reported in other cell systems: LPA enhanced internalization of LPA 1 and transferrin receptors via a clathrin- and cholesterol-dependent manner ( Urs et al, 2005 ); LPA stimulated micropinocytosis via Rho GTPases and subsequent actin modification in Entamoeba histolytica , an anaerobic parasitic amoebozoan ( Apte et al, 2022 ).…”
Section: Discussionmentioning
confidence: 83%
“…By this screening, we successfully identified EhRacM as a negative regulator of macropinocytosis (Figs 2A). To date, several studies have demonstrated specific roles of E. histolytica Rho proteins in endocytic pathways, such as EhRacA (21), EhRho1(20), EhRacG(22), and EhRho5 (EhRacD1 (19)) (37). This study is the first to identify EhRacM as a macropinocytosis-specific regulator, independent from other endocytic pathways.…”
Section: Discussionmentioning
confidence: 99%